Analysis of breath and skin gases emanating during exercise using an original biogas sampling system connected to an atmospheric pressure ionization mass spectrometer - Shimouchi, A.; Nose, K.; Shirai, M. (IEEE Sensors Journal, 2010)
Cardiopulmonary exercise testing is widely used in the field of sports and clinical medicine. Among the indices for evaluating exercise capacity, the anaerobic threshold is one of the most important parameters, often represented by the ventilatory threshold. The threshold, however, is sometimes not easy to determine. Yet, while more than several thousands kinds of chemical have been detected in human breath, there have been relatively few reports about the chemicals released within skin gas. In the present paper, we examined human breath and skin gas mass spectra data to explore the chemical compounds associated with anaerobic metabolism during exercise. Six healthy men, breathing purified artificial air via a two-way valve mouth piece and performing incremental bicycle ergometer exercises, were studied. Their breath was continuously analyzed using an atmospheric pressure ionization mass spectrometer (APIMS). On separate experimental days, skin gas from the palms of five subjects during the same exercise routine was monitored by an originally developed skin gas sampling system connected to the APIMS. The API mass spectra (represented by ion intensities at ${m}/{z} = {3} - {200}$ ) indicated numerous changing patterns between subject rest, warm up, ramp exercise and recovery periods. The exercise states caused remarkable increases to ion intensity. This was to within 7 and 6 kinds of m/z for breath and skin gas respectively. During recovery, by contrast, ion intensities gradually decreased. The changing ion intensity patterns displayed some similarity to oxygen consumption patterns.